STILISTIC AND SYNTACTIC VARIATION OF GERMAN PREPOSITIONS - E. L. Shubina (Vestnik MGIMO-Universiteta)
This work is devoted to the stylistic and syntactic variation of prepositions per and via in the publicistic style of modern German language. The similarity of German prepositions with the units of significant vocabulary in the aspect of variation is expressed through inherent in all level of words synonymic replacements. One of the special features of the prepositional system of modern German language is its openness, that is sun in the rapid replenishment at the expense of the transition of the prepositions borrowed from other languages. The pretexts per and via actively penetrate into social and political journalism together with the borrowed words and discover the combinability of both concrete and abstract nouns. Both prepositions are functionally semantic field of instrumentalnosti, discover the same regularity of use. But for proper names the combination with the preposition via. The stylistic variation of the considered prepositions consists in the selectivity of functional styles and in the variable use of the prepositions on the basis of the similar definitions. The analysis of the press materials has shown, that for the mentioned prepositions characteristically different case control. Despite the recommendations of grammarians, there prepositions are capable to connected to more than one form of this case. The preposition per manages not only accusative case, as it is indicated by the normative grammar, but also to dative. The most intensive variation of forms is peculared to the preposition via, which manages accusative, genitive and dative cases. Among the syntactic factors the greatest effects on the fluctuations in the use of prepositions in modern German language make an impact on structural-formal particulary, the presence/absence of the articles or a cover word before the managed noun, preposition/postposition of the preposition, the type of the declination combined with the preposition of the noun.